Analisis Keberlanjutan Usaha Padi Sawah Di Kecamatan Tugumulyo Kabupaten Musi Rawas Provinsi Sumatera Selatan Analisis - Ekopsi, Mahdi; Susatya, Agus; Brata, Bieng; Wiryono, Wiryono; Yurike, Yurike (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
This study aims to determine the sustainability status and sensitive attributes of each dimension in lowland rice cultivation in Tugumulyo District, Musi Rawas Regency, South Sumatra Province. This research was conducted in September - October 2021 in Tugumulyo District, Musi Rawas Regency, South Sumatra Province. Sustainability analysis is carried out using Multi Dimensional Scaling analysis which consists of 5 dimensions, namely ecological, socio-cultural, economic, technological and infrastructure, as well as legal and institutional dimensions. The results showed that the multidimensional sustainability index value of paddy farming in Tugumulyo District was 44.30 with a less sustainable status. Ecological, economic, socio-cultural as well as legal and institutional dimensions have a sustainability status classified as less sustainable. While the dimensions of technology and infrastructure are quite sustainable. Sensitive attributes on the ecological dimension include the suitability of paddy fields, the use of organic fertilizers and biological/biological pesticides. Sensitive attributes on the economic dimension include the incidence of crop failure, labor fees for farming, the availability of labor if needed and the price of pesticides for paddy rice farming. Sensitive attributes on the socio-cultural dimension include water conflicts between farmers or the practice of swift water pools, the level of labor absorption from rice farming, farmers' knowledge of calm lowland rice cultivation techniques and a culture of mutual cooperation in lowland rice cultivation such as cleaning irrigation canals. Sensitive attributes on the technology and infrastructure dimensions include the availability of supporting tools for lowland rice farming, availability of seeds, fertilizers, and pest control drugs for lowland rice diseases, standardization of rice quality and operational control of lowland rice cultivation tools. Sensitive attributes on the legal and institutional dimensions are the availability of microfinance schemes for lowland rice farming, the local government's budget for lowland rice farming and the presence of water regulatory officers. Keywords : Multidimensional, rice business, sensitive attribute, sustainability analysis